Progressive Muscle Relaxation for Sleep Quality in Menopausal Women's - Andriani, Anita Duwi; Berthy, Chanda Paramitha; Mulyaningsih, Erika Agung (Journal of Applied Nursing and Health, 2023)
Background: Problems that often occur in women who experience menopause psychologically are emotional disturbances, feelings of fear, anxiety, irritability, difficulty concentrating, depression, and impaired libido. Physiologically there are problems, including pain during intercourse, menstrual cycles and increasingly varied bleeding patterns, hot flashes (repeated periods of sweating), respiratory problems, vaginal dryness, dry skin, disturbed sleep patterns, and sleep quality. During the transition process of menopausal women, sleep quality is one of the most common and disturbing problems. This research aims to analyze the influence of Progressive Muscle Relaxation (PMR) on Sleep Quality in Menopausal Women. Methods: this research, using the purposive sampling technique, the researcher selected the respondents according to the inclusion criteria so that respondents have the same opportunity to be selected. In the intervention group, respondents were given progressive Muscle Relaxation (PMR). The sampling method is non-probability sampling with a purposive sampling technique. The number of samples is 17 respondents, carried out at menopause in Badang Village, Ngoro District, Jombang Regency on 04 - 19 July 2023. The analysis used the Wilcoxon Signed Ranks Test. Results: Statistical test results using the Wilcoxon Signed Ranks test obtained p value = .000, which means that there is an influence of progressive Muscle Relaxation (PMR) in improving Sleep Quality in Menopausal WomenDusun Wates Elderly PosyanduBadang Village, Ngoro District, Jombang Regency. Conclusion: Progressive Muscle Relaxation (PMR) is Effectively used to help improve sleep quality in postmenopausal women. Because the therapy trains the muscles of the head, neck, arms, and back in a controlled manner, it works against the sympathetic nervous system to achieve a relaxed and calm state and is easy to do.